Recurrence rate and predictors in non-ischemic reversible bradyarrhythmias - Dwivedi, Sudhanshu Kumar; Sharma, Akhil Kumar; Agrawal, Anant; Doomra, Kapil; Chaudhary, Gaurav Kumar; Chandra, Sharad; Bhandari, Monika; Vishwakarma, Pravesh; Pradhan, Akshyaya; Sethi, Rishi; Shukla, Ayush; Singh, Abhishek; et al. (Frontiers in Cardiovascular Medicine, 2024)
Objective Non-ischemic symptomatic reversible bradyarrhythmia is a poorly characterized yet common clinical challenge. This study aimed to assess the incidence and predictors of recurrence and the need for permanent cardiac pacing in patients with non-ischemic symptomatic reversible bradyarrhythmia. Methods This prospective single-center study enrolled 124 consecutive adult patients with non-ischemic symptomatic reversible bradyarrhythmia who were followed up for up to 24 months after conservative management during index hospitalization. The primary endpoint was a recurrence of bradyarrhythmia requiring permanent cardiac pacing. The secondary endpoint was a composite of recurrence requiring permanent pacing, readmission, or death. Univariate and multivariate analyses were conducted to determine the predictors of the endpoints. Results Sinus node and atrioventricular node diseases were seen in 66.1% and 33.9% of patients, respectively. The most common causes of bradyarrhythmia were negative chronotropic drugs (58.1%) and hyperkalemia (55.6%). Permanent pacing was required in 21.8% of patients after a recurrence. Advanced atrioventricular block at presentation (HR: 6.10, 95% CI: 2.45–15.20, p < 0.001) and bifascicular block at discharge (HR: 3.63, 95% CI: 1.58–8.33, p = 0.002) during index hospitalization were significant independent predictors of recurrence requiring cardiac pacing. Conclusion Non-ischemic symptomatic reversible bradyarrhythmia is associated with a high risk of recurrence. Permanent cardiac pacing should be considered during index hospitalization in patients with advanced atrioventricular block and/or bifascicular block.